Molecular genetic mapping in apricot - J. Salava; Y. Wang; B. Krška; J. Polák; P. Komínek; R.W. Miller; W.M. Dowler; G.L. Reighard; A.G. Abbott (Czech Journal of Genetics and Plant Breeding, 2002)
A genetic linkage map for apricot (Prunus armeniaca L.) has been constructed using amplified fragment length polymorphism (AFLP) markers in 80 BC1 individuals derived from a cross LE-3246 × Vestar. From 26 different primer combinations, a total of 248 AFLP markers were scored, of which, 40 were assigned to 8 linkage groups covering 315.8 cM of the apricot nuclear genome. The average interval between these markers was 7.7 cM. One gene (PPVres1) involved in resistance to PPV (Plum pox virus) was mapped. Two AFLP markers (EAA/MCAG8 and EAG/MCAT14) were found to be closely associated with the PPVres1 locus (4.6 cM resp. 4.7 cM). These markers are being characterized and they will be studied for utilization in apricot breeding with marker-assisted selection (MAS).